Combining the Sulcus Line and Posterior Condylar Axis Reduces Femoral Malrotation in Total Knee Arthroplasty. Issue 2 (16th February 2016) - Talbot, Simon; Chao, Tat Woon; Geraghty, Liam
Objectives: Femoral component malrotation is a common cause of patient dissatisfaction after total knee arthroplasty. The Sulcus Line (SL) is formed from multiple points along the floor of the trochlear groove, and has been shown to be more accurate than Whiteside Line. A trochlear alignment guide (TAG) is required to maintain the accuracy of the SL and allow intraoperative comparison of the SL and the posterior condylar axis (PCA). The hypothesis is that averaging these two landmarks will lead to less femoral malrotation. Methods: Surgery was performed in 50 patients using the TAG. The component was inserted at a position between the SL and PCA. An intraoperative photograph was taken of the distal cut surface of the femur showing the pin-holes representing the SL, the PCA and the final component position. These were compared to the component position achieved relative to the surgical epicondylar axis (SEA) on a postoperative CT scan. Comparison was made between the final component position and the position which would have been achieved using either the SL or PCA individually. The theoretical position which could be achieved by averaging the SL and PCA was also calculated. Results: The SEA was identified on CT scan in 46 cases. The component position was 0.7° (SD 1.5°), SL was -0.8° (SD 2.1°), PCA was 1.1° (SD 2.1°), the calculated average position between SL and PCA was 0.1° (SD 1.5°). There was a significant decrease in variance between both the component position and the calculated average when each was compared to the SL and PCA individually. The number of outliers greater than 3° from the SEA was also significantly less (p<0.05) for both the component position (3/46, 6%) and the calculated average position(1/46, 2%) when each was compared to the SL (10/46, 22%) and PCA (11/46, 24%) individually. The rotational alignment of the trochlear and posterior condyles diverged from each other more than 4° in 11/46 (24%). Conclusion: Averaging the SL and the PCA intraoperatively leads to decreased femoral component malrotation compared to the use of either landmark individually.